Evaluation of drying schedules for chalamite wood (Pinus pseudostrobus) - Aquino-González, Laura V.; Rodríguez-Ramírez, Juan; Méndez-Lagunas, Lilia L.; Sandoval-Torres, Sadoth (Instituto de Ecología, A.C., 2016)
The aim of this study is to analyze the kiln-drying of chalamite wood (Pinus pseudostrobus) using a 22 factorial design. Two drying schedule were applied: the first one was an intense schedule with temperatures from 76°C to 87°C, and the second one a soft schedule with temperatures from 60 °C to 82 °C; these schedules were applied with two air velocities: 2,05 ms-1 and 3,35 ms-1. Drying time and quality of wood were the responses evaluated. According to the results, the drying time is affected by the schedule intensity, and the wood quality depends on the drying schedule and air velocity. Statistically, it was observed that a drying schedule with temperatures from 76 °C to 87°C and air velocity of 3,35 ms-1 reduces the drying time and defects development in wood.